(3CUhd GdgfOSI hGdMSGHs - (3GdWhSj, CHh LYaQ, fUjQ GdOjf, eMeO Hf eMeO Hf GdMSf, J (B672 (3g`s ((3eMeO jhSas)
(3ChdgG (B:s
(3GdMeO ddg GdPj(B... (3GdGHJOGA(B... (3hHYO, acdeG aQZJ ef JMQjQ GdeLSWj QCjJ Cf CMQQ cJGH CUhd GdgfOSI hGdMSGH GdefShH dEbdjOS(B... (3Cbhd(B: (3GdcJGH jTJed Ydi NeS YTQI ebGdI(B...s
(3BNQgG (B:s
(3GKfJj YTQI bGYOI HgPG GdhLg aEf(B... (3bQjH ef eFI(B. (3hEP habfj Gddg JYGdi aj JMQjQ gPG GdcJGH MSH eG bUOJs
(3Hg QShe gfOSjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B7(3, U(B30s
(3GfXQ GdPQjYI Qbe(B: 471s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdJfLjes